Building plan approval by local authority (MDPM) / Wan Mohamad Shahril Afiq Wan Abdul Fatah - Wan Abdul Fatah, Wan Mohamad Shahril Afiq (Universiti Teknologi MARA, Perak, 2014)
This report briefly describes the process of building plan approval and problem occurred during the application process. It produce according to a five-month experience at a Pasir Mas District Council (MDPM). The objective of the report is to understand the documents required throughout the application for Building Plan Approval, to understand the application required by the Building Department of Pasir Mas District Council and to identify factors of failure in applying building plan approval by both client and MDPM. ln this report, there have four method of study. First is internet, examples of work related to the scope of the research that was made as a reference to enable me to complete this report. Secondly is observation, it's helping to see the real situation of the work of doing building plan approval. Thirdly is interview, it is a bit of help in gather information about the research topic of the process of building plan approval by the local authority. Lastly is journal and books, it can obtain a lot of detailed information not only about building plan approval but also the knowledge about construction work.